Biophysical studies of membrane protein structure and function - Dijkman, P; Patricia M. Dijkman (2014)
Membrane proteins play a key role in numerous physiological processes such as transport, energy transduction in respiratory and photosynthetic systems, and signal transduction, and are of great pharmaceutical interest, comprising more than 60% of known drug targets. However, crystallisation of membrane proteins, and G protein-coupled receptors (GPCRs) in particular, still relies heavily on the use of protein engineering strategies, which have been shown to hamper protein activity. Here, a range of biophysical methods were used to study the structure and function of two membrane proteins, a prokaryotic peptide transporter, PepTSo and a GPCR, neurotensin receptor 1 (NTS1), using different membrane reconstitution methods to study the proteins in a native-like environment. Firstly, using the pulsed electron paramagnetic resonance (EPR) method of double electron-electron resonance (DEER) the conformation of PepTSo reconstituted into lipid bilayers was assessed and compared to previous structural data obtained from crystallography and modelling. The influence of the membrane potential and the presence of substrate on the conformational heterogeneity of this proton-coupled transporter were investigated. Secondly, NTS1 purification was optimized for biophysical study. Cysteine mutants were created and a labelling protocol was developed and optimized for fluorophore and nitroxide labelling studies. NTS1 was then studied by continuous-wave EPR, to assess the influence of ligand on local protein dynamics, and to assess the structure of a receptor segment known as helix 8, that was proposed to be an α-helix, but was only observed to be helical in one of the NTS1 crystallographic studies. Ensemble and single-molecule Förster resonance energy transfer (FRET), and DEER were combined to study the dimerisation behaviour of NTS1, showing novel dynamics of the interfacial associations. Finally, the signalling mechanism of NTS1 was also investigated using microscale thermophoresis (MST) to assess the affinity of the receptor for G protein in vitro in the absence of ligand, or in the presence of agonist or antagonist. MST measurements were performed in detergent and in nanodiscs of different lipid compositions, to assess the influence of the lipid environment on receptor function. In summary, this thesis demonstrates the potential of biophysical techniques to study various aspects of membrane protein structure and function in native-like lipid systems, complementing e.g. structural data obtained from crystallographic studies with functional data for membrane proteins in more native environments, as well as shedding light on protein dynamics. The work presented here provides novel insights into PepTSo transport, and in particular into NTS1 structure, signalling, and oligomerisation, opening up several avenues for future research.